Porous Nanogold/Polyurethane Scaffolds with Improved Antibiofilm, Mechanical, and Thermal Properties and with Reduced Effects on Cell Viability: A Suitable Material for Soft Tissue Applications - Paez-Collio, M; Paez-Collio, M; Cerda-Villablanca, E; Azocar-Guzman, M; Azocar-Guzman, M (American Chemical Society, 2018)
The use of implants carries on a series of problems, among them infections, poor biocompatibility, high levels of cytotoxicity, and significant mechanical differences between implants and host organs that promote stress shielding effects. These problems indicate that the materials used to make implants must meet essential requirements and high standards for implantations to be successful. In this work, we present the synthesis, characterization and evaluation of the antibiofilm, mechanical, and thermal properties, and cytotoxic effect of a nanocomposite-based scaffold on polyurethane (PU) and gold nanoparticles (AuNPs) for soft tissue applications. The effect of the quantity of AuNPs on the antibacterial activity of nanocomposite scaffolds was evaluated against Staphylococcus epidermidis and Klebsiella spp., with a resulting 99.99% inhibition of both bacteria using a small quantity of nanoparticles. Cytotoxicity was evaluated with the T10 1/2 test against fibroblast cells. The results demonstrated that porous nanogold/PU scaffolds have no toxic effects on fibroblast cells to the 5 day exposition. With respect to mechanical properties, stress-strain curves showed that the compressive modulus and yield strength of PU scaffolds were significantly enhanced by AuNPs (by at least 10 times). This is due to changes in the arrangement of hard segments of PU, which increase the stiffness of the polymer. Thermogravimetric analysis showed that the degradation onset temperature rises with an increase in the quantity of AuNPs. These properties and characteristics demonstrate that porous nanogold/PU scaffolds are suitable material for use in soft tissue implants. © 2018 American Chemical Society.